No sex education please, we're Arab - McGrath, Cam (Arab American news = al-Akhbar al-ʻArabīyah al-Amīrkīyah, 2010)
Egypt's education ministry has instructed schools not to teach lessons on "reproduction and propagation methods," "pollination and fertilization" genetics, and anatomical illustrations of the male and female reproductive systems. Teachers were ordered to disregard chapters on these subjects in existing biology textbooks, and new textbooks have been printed that omit the lessons. "Definitely there will be social and health consequences," says Dr. Amai Abdel Hadi, an outspoken advocate of reproductive health rights. "There will be more misconceptions about sex, marital disharmony and sexual harassment. . . and the prevalence of STDs (sexually transmitted diseases) will increase." "In the 1960s and 1970s, when people discussed sexuality, the focus was on good and bad relationships," she told IPS. "Now it is only about what is halal (permissible) or haram (sinful), which moves the whole issue into the religious realm."